Impacts of palm oil trade on ecosystem services: Cameroon as a case study - Acobta, Ada N.; Ayompe, Lacour M.; Egoh, Benis N. (Frontiers in Sustainable Food Systems, 2023)
Palm oil (PO) producing countries are expanding oil palm cultivated areas to meet growing demands at the expense of tropical forests and the ecosystem services (ES) they provide. Current responses to the growing call for sustainable PO trade are based on environmental impacts such as deforestation, partly because most social impacts have not been studied. These responses are based on information from Asia and South America since little has been done in Africa. This study fills these gaps by synthesizing the impacts of PO trade on ES from peer-reviewed and gray literature.Our case study is Cameroon, which harbors part of the Congo basin forest and experiences fast deforestation rates. Fifty-three sources of literature were used for this study (53% peer-reviewed and 47% gray literature). We found that oil palm cultivation was reported to negatively affect fifteen ecosystem services in 147 instances (85%) and positively affect seven ecosystem services in 25 instances (15%).. The majority of negative impacts were on carbon sequestration and climate regulation (20%), habitat quality (13%) and genetic diversity (13%). The most positive impact was on food provision (8%). These results highlight the trade-offs between food provision and other ES. While current policy responses have focused on environmental impacts, many negative social impacts are associated with PO trade that should be addressed within new policy tools.